The Impact of Entrepreneurship Competitions on Entrepreneurial Competence of Chinese College Students - Wang, Jing; Guo, Yang; Zhang, Mengting; Li, Ningning; Li, Kexin; Li, Ping; Huang, Leilei; Huang, Yangjie (Frontiers in Psychology, 2022)
Entrepreneurship competitions are an important way to implement entrepreneurship education in universities and the main way for many students improve their entrepreneurial competence. To clarify the mechanism of the role of entrepreneurship competition on the entrepreneurial competence of university students, based on data from a sample of 170,764 university students from 31 provinces in China, this study constructs a moderated mediation model that focuses on the mediating role of entrepreneurial spirit (ES) in entrepreneurial competition (ECompetition) and entrepreneurial competence (ECompetence) and the moderating role of entrepreneurial practice (EP). The results showed that ECompetition found to have a significant positive predictive effect on ECompetence. ES plays a mediating role in the relationship between ECompetition and competence. The direct predictive effect of ECompetition on ECompetence and the mediating effect of ES on their relationship is moderated by EP. The results provide a new perspective on the impact of entrepreneurship competition on college students’ entrepreneurial competence and expands the experiential learning theory in entrepreneurship education.